Effectiveness of two different recovery process on blood lactate removal pattern of soccer players - Rupali Katoch; SM Farooque; Krishnendu Dhar; Prasanta Kumar Das (Pedagogy of Physical Culture and Sports)
Background and Study Aim. Soccer is a high-intensity intermittent sport that requires players to alternate between explosive activity and recovery. This often leads to significant blood lactate accumulation, a by-product of anaerobic metabolism, which can impair performance by inducing muscular fatigue and reducing the ability to sustain optimal effort. This study aimed to examine the effect of two different recovery processes on the blood lactate removal pattern of soccer players in Tripura.